Law enforcement information sharing: A Florida case study - Reynolds, K. Michael (American journal of criminal justice, 2006)
Many attempts have been made over the last several decades to improve communication among law enforcement agencies. This article is a case study of a “low-level” data sharing project in Florida that could serve as a national model. The Florida Law Enforcement Data Sharing Consortium is a partnership between the University of Central Florida and more than one hundred law enforcement agencies. It offers an inexpensive, yet technically advanced alternative to the proprietary data sharing model. Its distributed architecture was endorsed by the Markle Foundation, the 9/11 Commission, and the 2004 National Security Act. Civil liberties concerns raised by this and other types of data sharing projects are discussed.